REDUCTION OF SETUP TIME IN THE DISASSEMBLY PROCESS WITH A SINGLE MINUTE EXCHANGE OF DIES (SMED) APPROACH AND FUZZY FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Allyssa, Syifa; Muqimuddin, Muqimuddin; Pratikno, Faishal Arham (Center for Study and Journal Management FTI UMI, 2024)
PT XYZ, a company specializing in heavy equipment component remanufacture, is committed to ensuring that its processes run quickly and efficiently. However, from 2022 to 2023, the disassembly engine process exceeded the average processing time. Observations revealed that 24% of the time was categorized as waste setup time, necessitating a more objective reduction. This research aims to determine the actual total setup time, internal and external activities, and time reduction using the SMED and Fuzzy FMEA methods. The disassembly process includes the main disassembly, sub disassembly 1, and sub disassembly 2. Single Minute Exchange of Dies (SMED) is employed to identify and reduce setup time by distinguishing between internal and external activities. Additionally, this research integrates the SMED method with Fuzzy Failure Mode and Effect Analysis (FMEA) to identify potential risks in setup activities and determine which internal activities can be modified. Changes to external activities will be analyzed using the 5-Why's method to identify root causes and find solutions. Observations revealed that the average disassembly engine setup time was 20 hours and 12 minutes, consisting of 25 internal activities and 56 external activities. The SMED method resulted in an 18% reduction in setup time, and when combined with the Fuzzy FMEA method, the reduction reached 59%, equivalent to 8 hours and 17 minutes.